1994
DOI: 10.1089/thy.1994.4.333
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of Autoimmune Thyroid Disease: A Review

Abstract: Lymphocytic infiltration of the thyroid gland is the pathologic hallmark of autoimmune thyroid disease. Lymphoid cells are seen in the stroma of glands affected by Graves' disease. However, large lymphoid infiltrates are characteristic of that spectrum of diseases conveniently termed chronic lymphocytic thyroiditis. In this review, the pathology of the various subtypes of chronic thyroiditis is enumerated, including recently defined lesions, i.e., painless thyroiditis, thyroiditis associated with interleukin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0
8

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 101 publications
0
73
0
8
Order By: Relevance
“…27,30,31 As a result of the histological similarity, confusion has been noted in the literature regarding Riedel's thyroiditis and fibrous variant of Hashimoto's thyroiditis. 23 Most recently, an association between Riedel's thyroiditis and IgG4-related disease has been described by Dahlgren et al 32 They demonstrated excessive numbers of the IgG4-positive plasma cells in Riedel's thyroiditis samples. This observation would seem to further blur the distinction between the IgG4-related Hashimoto's thyroiditis and Riedel's thyroiditis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…27,30,31 As a result of the histological similarity, confusion has been noted in the literature regarding Riedel's thyroiditis and fibrous variant of Hashimoto's thyroiditis. 23 Most recently, an association between Riedel's thyroiditis and IgG4-related disease has been described by Dahlgren et al 32 They demonstrated excessive numbers of the IgG4-positive plasma cells in Riedel's thyroiditis samples. This observation would seem to further blur the distinction between the IgG4-related Hashimoto's thyroiditis and Riedel's thyroiditis.…”
Section: Discussionmentioning
confidence: 95%
“…The most widely recognized subgroup is referred to as the fibrous variant of Hashimoto's thyroiditis, which accounts for approximately 10% of the Hashimoto's thyroiditis cases. 23 Katz and Vickery 2 defined this lesion in 1974 and proposed the following diagnostic criteria: (1) a marked fibrous replacement of more than one-third of the thyroid parenchyma and (2) changes typical of Hashimoto's thyroiditis in the remaining tissue. They also demonstrated that fibrous variant of Hashimoto's thyroiditis reveals a series of clinical features that are quite distinct from those of typical Hashimoto's thyroiditis, including a firm goiter (often presenting with a notable recent enlargement), frequent diagnostic confusion with a malignancy, a marked elevation in the tanned red cell titer and thyroglobulin, and thyroid function tests often indicating hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Follicular cell metaplasia, ranging from pale pink cells with abundant cytoplasm to true HCs with the characteristic granular, deeply eosinophilic cytoplasm, is commonly seen. Reflecting the apparent need for cells to accumulate significant numbers of mitochondria over a prolonged period of time, HC metaplasia is rarely seen in the juvenile form of CLT [16]. Although the disease entity in which Askanazy first described HCs, diffuse toxic goiter (Graves' disease), typically does not contain an abundance of HCs, they may be seen in cases of long-standing Graves' disease, in older individuals with the disease, or in patients with a history of Graves' disease who have undergone radioactive iodine ablation and subsequently develop nodular thyroid disease [9].…”
Section: Thyroid Pathology Associated With Hcsmentioning
confidence: 99%
“…Tezuka et al (23) proposed another hypotheses, which was that perfusion due to augmented intrathyroidal blood flow and vascularity (characteristic of GD) might account for the significantly higher ADC values of GD, as compared with those of subacute thyroiditis and Hashimoto thyroiditis. It is also evident that, as in PT, lymphocytic infiltration is a prominent feature in subacute thyroiditis and Hashimoto thyroiditis (29), which will result in hypercellularity. This may explain why the results of the present study are consistent with those of Tezuka et al MR imaging is non-invasive, since no injection of contrast material is required.…”
Section: Discussionmentioning
confidence: 99%
“…PT is a syndrome of thyrotoxicosis due to the release of preformed thyroid hormones from disrupted thyroid follicles. The diffuse infiltration of the thyroid by lymphocytes implies that it is also an autoimmune disorder (28,29). RAIU testing or thyroid scintigraphy is of high diagnostic value for differentiating between GD and PT, and has been demonstrated to be reliable (11-14); however, RAIU and thyroid scintigraphy reflect only one type of change in the pathogenesis of the two diseases.…”
Section: Discussionmentioning
confidence: 99%